2020
DOI: 10.1080/23311975.2020.1817288
|View full text |Cite
|
Sign up to set email alerts
|

Product involvement, WOM and eWOM in the fast food industry: A young adult perspective in an emerging African economy

Abstract: This study investigates the relationship between product involvement, WOM, and eWOM in the fast food industry between two sub-groups of young adult consumers in South Africa. A quantitative design was followed, with primary data (n = 201) gathered from respondents using a self-administered questionnaire. The results suggest that product involvement exerts a positive and significant influence on WOM and eWOM in the case of both young adult sub-groups. There is also no difference in the perceptions of the two su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 55 publications
(86 reference statements)
2
10
0
Order By: Relevance
“…Wei and Huang (2017) investigated food traceability systems potential as elevators of best practice in corporate social responsibility for quickservice food restaurants in Japan. Ledikwe et al (2020) assessed the effect of word of mouth and electronic word of mouth in the fast food industry from a South African context. Wu et al (2019) conducted a study in Taiwan that looked at the connections between restaurant attachment, experiential relationship efficiency, and experiential relationship intentions.…”
Section: Introductionmentioning
confidence: 99%
“…Wei and Huang (2017) investigated food traceability systems potential as elevators of best practice in corporate social responsibility for quickservice food restaurants in Japan. Ledikwe et al (2020) assessed the effect of word of mouth and electronic word of mouth in the fast food industry from a South African context. Wu et al (2019) conducted a study in Taiwan that looked at the connections between restaurant attachment, experiential relationship efficiency, and experiential relationship intentions.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, confirmed that product involvement can also positively influence eWOM intention. Similarly, environmental factors have also been confirmed to generate purchase intentions (Ledikwe et al, 2020;Sherman et al, 1997). Durna et al (2015) confirmed that physical servicescape elements can positively affect eWOM intentions.…”
Section: Servicescape Ewom and Re-purchase Intentionsmentioning
confidence: 71%
“…To examine the impact of perceived quality on consumer purchase intention, items were extracted from [ 63 ] and [ 69 ]. Items for measuring price fairness were adapted from [ 39 ]. All the independent and dependent variables were measured on a 7-point scale ranging from 1 = strongly disagree to 7 = strongly agree .…”
Section: Methodsmentioning
confidence: 99%
“…Consumer involvement is defined as a person’s perceived relevance of the specific products based upon inherent interest, values, and needs [ 72 ]. Product involvement is determined by how far the consumer considers the product to be important to their life [ 28 ] and their subjective evaluation of its perceived value [ 39 ]. Involvement has been described as the amount of arousal or interest that is generated by a situation, object, or stimulus; it represents an individual-level variable [ 45 ].…”
Section: Literature Reviewmentioning
confidence: 99%